Challenges of implementing nutrition policy in Papua New Guinea - Helen Palik (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Purpose: The national nutrition policy 1995 was reviewed to address the chronic nutrition problems that existed for decades. The problems revealed from National Nutrition Survey 2005-2006, showed that about 44% of the children from ages 6 -59 months in Papua New Guinea (PNG) are physically stunted, 5 % are wasted and 18% are underweight. It also showed that 48 % are anaemic, of which 28% have iron deficiency. The proportion of children with vitamin A deficiency accounted for 25.6% of the study population. Method: The multi-sectoral approach was applied to review Nutrition Policy 2016 in order improve nutrition for all Papua New Guineans through evidence-based, coordinated nutrition approaches that optimises resources and aligns actions and to improve nutrition for all Papua New Guineans through evidence-based, coordinated nutrition approaches that optimises resources and aligns actions enabling smart, fair, wise, healthy and happy nation through improved nutrition and health outcomes for all citizens of PNG. Results: Proportion of health workers to the population at lower level is inadequately distributed at the primary health care level and many times one staff is doing many things at the same time and there is often less focus to concentrate on one specific job to produce better expected results. Many managers are working in difficult working conditions with changing environment and poor infrastructure, Managers face challenges in the areas of personal, technical performance, environment changes and survival and growth (Shortell & Kaluncy 2000), many of the managers do not know what exactly they are supposed to do. “Many challenges await. There are no panaceas for fixing our healthcare system”(Shalala D1). In PNG, there are many reasons why very good policies that have clear goals and visions are not implemented successfully as expected at all levels especially at the lower level where many of the outcomes are measured. Many blame the poor health system as a result of political influences while others have different opinions about various contributing factors including the WHO six building blocks which may have affected the policy implementation resulting in favourable or bad outcomes. Conclusion: Strengthen M & E system by the use of latest IT Technology (telemedicine) to asses outcomes and also monitors progress of policy implementation ,capturing important indicators and or interventions measured against the policies indicators, thus user friendly.